Some Inhibitors of the Fibrinogen-Fibrin Conversion - Elias, T. P; Iyer, G. Y. N (Thrombosis and Haemostasis, 1967)
1. The inhibitory effect of a number of substances on the fibrinogen-thrombin reaction has been studied. The effect is best observed at pH 7.4 using calcium free dilute thrombin. Ca++ reduces the effect; Mg++ is less effective than Ca++. The optimum concentration of Ca++ is 0.5 to 1 mM.2. Preincubation with fibrinogen increases the effect of EDTA, sulphite and thioglycollate on the thrombin time. These compounds also appear to alter fibrinogen and thereby retard the conversion of fibrinogen to fibrin monomer.3. Preincubation of thrombin with these substances does not result in loss of TAME esterolytic activity or in prolongation of thrombin time of fibrinogen.4. Inhibitors of the fibrinogen-thrombin reaction retard the polymerisation of fibrin monomer to fibrin and also the attendant increase in opacity.5. The inhibitors of the fibrinogen-thrombin reaction studied appear to exert their effect mostly at the stage of polymerisation of the fibrin monomer. Calcium ions largely reverse the inhibition of this step.